Design, synthesis, and bioevaluation of viral 3C and 3C-like protease inhibitors - Prior, Allan M.; Kim, Yunjeong; Weerasekara, Sahani; Moroze, Meghan; Alliston, Kevin R.; Uy, Roxanne Adeline Z.; Groutas, William C.; Chang, Kyeong-Ok; Hua, Duy H. (My University, 2013)
A class of tripeptidyl transition state inhibitors containing a P1 glutamine surrogate, a P2 leucine, and a P3 arylalanines, was found to potently inhibit Norwalk virus replication in enzyme and cell based assays. An array of warheads, including aldehyde, α-ketoamide, bisulfite adduct, and α-hydroxyphosphonate transition state mimic, was also investigated. Tripeptidyls 2 and 6 possess antiviral activities against noroviruses, human rhinovirus, severe acute respiratory syndrome coronavirus, and coronavirus 229E, suggesting a broad range of antiviral activities.
Keywords: Viral 3C and 3C-like protease inhibitors; Norovirus; Human rhinovirus; Severe acute respiratory syndrome coronavirus; Conronavirus 229E